Expression of toll like receptor 8 (TLR8) in specific groups of mouse hippocampal interneurons. - Lennart Seizer; Sadegh Rahimi; Sandra Santos-Sierra; Meinrad Drexel (PLoS ONE)
Toll-like receptors (TLR) are one of the main constituents of the innate immune system in mammals. They can detect conserved microbial structures (pathogen-associated molecular patterns) and host-derived ligands that are produced during cellular stress and damage (danger-associated molecular patterns) and may then initiate an intracellular signaling cascade leading to the expression of pro-inflammatory cytokines and immediate immune responses. Some TLR (TLR1, 2, 4, 5, and 6) are expressed on the cell surface while others (TLR3, 7, 8 and 9) are present on the surface of endosomes and their ligands require internalization before recognition is possible. Several TLR have also been detected in neurons where they may serve functions that are not related to immune responses. TLR2, 3, and 4 have been described in cortical neurons and, for TLR4, a seizure-promoting role in epilepsies associated with inflammation has been shown. TLR3, 7, and 8 expressed in neurons seem to influence the growth or withdrawal of neurites and robust activation of TLR8 in neurons may even induce neuronal death. The goal of the current study was to investigate the expression of TLR8 in the hippocampus of mice during postnatal development and in adulthood. We focused on three functionally distinct groups of GABAergic interneurons characterized by the expression of the molecular markers parvalbumin, somatostatin, or calretinin, and we applied double fluorescence immunohistochemistry and cell counts to quantify co-expression of TLR8 in the three groups of GABA-interneurons across hippocampal subregions. We found subregion-specific differences in the expression of TLR8 in these interneurons. During postnatal development, TLR8 was detected only in mice older than P5. While only a small fraction of hippocampal calretinin-positive interneurons expressed TLR8, most parvalbumin-positive interneurons in all hippocampal subregions co-expressed TLR8. Somatostatin-positive interneurons co-expressing TLR8 were mainly present in hippocampal sector CA3 but rare in the dentate gyrus and CA1. High expression of TLR8 in parvalbumin-interneurons may contribute to their high vulnerability in human temporal lobe epilepsy.